Effects of high intensity interval training on sustained reduction in cardiometabolic risk associated with overweight/obesity: A randomized trial - Monique Mendelson; Samarmar Chacaroun; Sébastien Baillieul; Stéphane Doutreleau; Michel Guinot; Bernard Wuyam; Renaud Tamisier; Jean-Louis Pépin; François Estève; Damien Tessier; Samuel Vergès; Patrice Flore (Elsevier, 2022)
Background/Objectives: Considering the potential greater cardiocirculatory effects of high intensity interval training (HIIT), we hypothesized that a 2-month supervised high volume short interval HIIT would induce greater improvements in CRF and cardiometabolic risk and increase long-term maintenance to physical activity compared to isocaloric moderate intensity continuous training (MICT) in overweight/obesity. Methods: Sixty (19 females) subjects with overweight/obesity were randomized to three training programs (3 times/week for 2 months): MICT (45 min, 50% peak power output-PPO), HIIT (22 × 1-min cycling at 100% PPO/1-min passive recovery) and HIIT-RM (RM: recovery modulation, i.e. subjects adjusted passive recovery duration between 30s and 2 min). After the intervention, participants no longer benefited from supervised physical activity and were instructed to maintain the same exercise modalities on their own. We assessed anthropometrics, body composition, CRF, fat oxidation, lipid profile, glycemic balance, low-grade inflammation, vascular function, spontaneous physical activity and motivation for eating at three time points: baseline (T0), 4 days after the end of the 2-month supervised training program (T2) and 4 months after the end of the training program (T6). Results: HIIT/HIIT-RM induced greater improvement in VO2peak (between +14% and +17%), power output at ventilatory thresholds and at maximal fat oxidation rate (+25%) and waist circumference (−1.53 cm) compared to MICT and tended to decrease insulin resistance. During the four-month follow-up period during which exercise in autonomy was prescribed, HIIT induced a greater preservation of CRF, decreases in total and abdominal fat masses and total cholesterol/HDL. Conclusion: We have shown greater short-term benefits induced by a high volume short interval (1 min) HIIT on cardiorespiratory fitness and cardiometabolic risk over an isocaloric moderate intensity continuous exercise in persons with overweight/obesity. We also showed greater long-term effects (i.e. after 4 months) of this exercise modality on the maintenance of CRF, decreases in total and abdominal fat masses and total cholesterol/HDL.